INFORMASI AKUNTANSI DIFERENSIAL SEBAGAI ALAT PENGAMBILAN KEPUTUSAN MENYEWA ATAU MEMBELI GEDUNG PADA PT. BPR MILLENIA KANTOR CABANG PAAL DUA - Kotambunan, Miranda Ellora; Nangoi, Grace B; Pontoh, Winston (Universitas Sam Ratulangi, 2020)
Decision making is the selection of one of the various alternative actions available. In choosing an alternative, management requires precise and accurate information to reduce the possibility of failure of decisions that will be taken by the company. Differential accounting information is very suitable to be used in the selection of several alternatives. The purpose of this study is to determine whether differential accounting information can be used as a decision-making tool so that companies can decide whether to rent or buy a building as a place to operate its branch offices. This research uses descriptive qualitative method by collecting data through interviews and documentation. The results showed that differential accounting information as a decision-making tool can be applied at PT. BPR Millenia Paal Dua Branch Office and the cost to rent a building is lower than buying a building.